The Study on the Thought of Realism in International Relations Contained in The Prince - Wang, Baisong (IJRDO - Journal of Social Science and Humanities Research, 2019)
Realism is a paradigm of international relations theories. For this paradigm, the earliest modern argument in history can be traced back to The Prince written by Niccolo Machiavelli in the Renaissance. In this book, he put forward many thoughts of realism in international relations such as theory of evil humanity, supremacy of national interests, power politics, diplomatic trickery and etc. These thoughts have been recognized as the origin of realism of Western international relations, so we should have a deep understanding of them to further study Western realism and foreign policy.